Leading professional practice in education - Wise, Christine; Bradshaw, Pete; Cartwright, Marion; Open University (London : SAGE Publications Ltd, 2013)
Written by leading academics, this volume provides an overview of key contemporary themes in educational leadership. It focuses on developing professional capacity, organisational improvement and the implementation of change, looking at theoretical frameworks and concepts, recent research studies and case examples of effective practice.
Published in association with the Open University.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Educational leadership; School management and organization